INTRODUCTION TO PRAYER MOVEMENTS: EFFECTIVENESS OF TWO-DIMENSIONAL TEACHING AIDS AT AL-RAHMAH SUBULUSSALAM KINDERGARTEN, ACEH - Muthmainnah Ismail; Lina Amelia; Heliati Fajriah; Muhammad Faisal; Siti Aisyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Prayer is an important act of worship that must be introduced from an early age. Based on initial observations at TKN Al-Rahmah, children are not yet able to recognize prayer movements well, because the introduction does not use interesting props. So this research aims to determine whether or not the introduction of prayer movements using two-dimensional teaching aids at TKN is effective. Experimental type quantitative research with a one-group pretest-posttest design was carried out on 20 class B children as samples and used observation and documentation sheets for data collection. Data analysis has proven that the pre-test score is 46% and the post-test 70.25%. So the results of the hypothesis test showed that the tcount ˃ttable is 78.22 ˃ 1.729, meaning that Ha is accepted and Ho is rejected. Based on these data, it can be concluded that the use of two-dimensional teaching aids is effective in introducing prayer movements to children at TKN PKK Al-Rahmah Subulussalam.